2015 17th International Conference on Transparent Optical Networks (ICTON) 2015
DOI: 10.1109/icton.2015.7193509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Mamdani and Sugeno fuzzy inference systems for the mitigation of environmental temperature variations in OCDMA-PONs

Abstract: This paper presents a comparative study between the Mamdani and Sugeno fuzzy inference systems (FIS) for intelligent traffic transmission over optical code-division multiple-access (OCDMA) network architectures. This FIS is capable of mitigating environmental temperature variation effects in the transmission link which are known to play an important role in the overall performance of the network. The paper outlines the basic difference between both Mamdani and Sugeno type FIS for this approach. The results hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similar comparative studies were conducted in various fields, such as optical [19] and wireless [20] networks, magnetic bearing system control [21], chaotic time series prediction [22], evaluation of user experience for specific applications [23], and streamflow prediction in the hydrological field [24]. Although Takagi-Sugeno usually showed better results, the research in the hydrological domain showed that the Mamdani FIS is more suitable.…”
Section: Literature Reviewmentioning
confidence: 71%
“…Similar comparative studies were conducted in various fields, such as optical [19] and wireless [20] networks, magnetic bearing system control [21], chaotic time series prediction [22], evaluation of user experience for specific applications [23], and streamflow prediction in the hydrological field [24]. Although Takagi-Sugeno usually showed better results, the research in the hydrological domain showed that the Mamdani FIS is more suitable.…”
Section: Literature Reviewmentioning
confidence: 71%
“…Fuzzy Inference Systems are based on two methods: the Mamdani Fuzzy Inference technique [21,[35][36][37][38][39][40] and the Takagi-Sugeno-Kang Inference method [35,36,38,39,[41][42][43][44][45][46][47][48]. The major difference between them lies in the consequent fuzzy rules and defuzzification procedures; the Mamdani Inference method uses fuzzy sets as rule consequent, while Sugeno Inference considers linear functions of input variables.…”
Section: Mamdani Fuzzy Inference Mppt Controller Designmentioning
confidence: 99%